Donors for nerve transplantation in craniofacial soft tissue injuries - Sun, Sishuai; Lu, Di; Zhong, Hanlin; Li, Chao; Yang, Ning; Huang, Bin; Ni, Shilei; Li, Xingang (Frontiers in Bioengineering and Biotechnology, 2022)
Neural tissue is an important soft tissue; for instance, craniofacial nerves govern several aspects of human behavior, including the expression of speech, emotion transmission, sensation, and motor function. Therefore, nerve repair to promote functional recovery after craniofacial soft tissue injuries is indispensable. However, the repair and regeneration of craniofacial nerves are challenging due to their intricate anatomical and physiological characteristics. Currently, nerve transplantation is an irreplaceable treatment for segmental nerve defects. With the development of emerging technologies, transplantation donors have become more diverse. The present article reviews the traditional and emerging alternative materials aimed at advancing cutting-edge research on craniofacial nerve repair and facilitating the transition from the laboratory to the clinic. It also provides a reference for donor selection for nerve repair after clinical craniofacial soft tissue injuries. We found that autografts are still widely accepted as the first options for segmental nerve defects. However, allogeneic composite functional units have a strong advantage for nerve transplantation for nerve defects accompanied by several tissue damages or loss. As an alternative to autografts, decellularized tissue has attracted increasing attention because of its low immunogenicity. Nerve conduits have been developed from traditional autologous tissue to composite conduits based on various synthetic materials, with developments in tissue engineering technology. Nerve conduits have great potential to replace traditional donors because their structures are more consistent with the physiological microenvironment and show self-regulation performance with improvements in 3D technology. New materials, such as hydrogels and nanomaterials, have attracted increasing attention in the biomedical field. Their biocompatibility and stimuli-responsiveness have been gradually explored by researchers in the regeneration and regulation of neural networks.